Failure is a great teacher - Luhana, Rakeshkumar (Research and Humanities in Medical Education, 2021)
I have been practising neurosurgery for the past fifteen years, and have acquired expertise in keyhole spinal surgery. In this narrative, I share my experience with a patient who had a prolapsed inter-vertebral disc, and who developed complications after surgery.